2006
DOI: 10.17660/actahortic.2006.726.90
|View full text |Cite
|
Sign up to set email alerts
|

Determi̇nati̇on of Effects of Plant Growth Regulator Appli̇cati̇ons on Alternate Beari̇ng i̇n Pi̇stachi̇os Under Sui̇table Growi̇ng Condi̇ti̇ons

Abstract: This study was carried out on Uzun and Siirt pistachio cultivars present at the Pistachio Research Institute orchards. After the most suitable pruning, fertilization and irrigation practices, different plant growth regulators were sprayed on entire trees at the different doses, and effects of plant growth regulators on alternate bearing were investigated. In the study, 10, 25 and 50 ppm 1-Naphthaleneacetic acid (NAA), 25 ppm Nbenzyl-9-(2-tetra-hydropyranyl) adenine (BA) and 0.25% urea were used, and 0.25% urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
7
1
Order By: Relevance
“…Plant growth regulators have been used in pistachio fruit production for influencing flowering, fruit set, and flower bud abscission. These regulators have also been used to influence flowering, abscission, fruit quality factors like peel quality and color, fruit size, and juice quality, and to improve total soluble solids in different pistachio species (Takeda and Crane, 1980;Ferguson and Maranto, 1989;Vemmos et al, 1994;Ferguson, 1998, 2001;Cetinkaya, 2004;Acar et al, 2006;Okay et al, 2011). The primary natural auxin, indole-3-acetic acid, is produced mostly in subapical regions of actively growing shoots, young leaves, and developing embryos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant growth regulators have been used in pistachio fruit production for influencing flowering, fruit set, and flower bud abscission. These regulators have also been used to influence flowering, abscission, fruit quality factors like peel quality and color, fruit size, and juice quality, and to improve total soluble solids in different pistachio species (Takeda and Crane, 1980;Ferguson and Maranto, 1989;Vemmos et al, 1994;Ferguson, 1998, 2001;Cetinkaya, 2004;Acar et al, 2006;Okay et al, 2011). The primary natural auxin, indole-3-acetic acid, is produced mostly in subapical regions of actively growing shoots, young leaves, and developing embryos.…”
Section: Discussionmentioning
confidence: 99%
“…(Ferguson and Maranto, 1989;Ak and Kaska, 1992;Tekin, 1992;Weinbaum et al, 1994;Acar et al, 2006;Gunes et al, 2010;Cetinkaya et al, 2018). Subsequently, the effects of plant growth regulators, carbohydrates, polyamines, and phenolic compounds were also studied, and recently, molecular and biotechnology studies have been carried out to solve the issue of alternate bearing in pistachios (Crane and Nelson, 1971;Nzima et al, 1997;Vemmos, 1999a;Acar et al, 2006;Teale et al, 2006;Acar et al, 2011;Okay et al, 2011;Cetinkaya and Ozguven, 2016;Gundesli et al, 2019). Monselise and Goldschmidt (1982) described the possible endogenous (hormonal) factors that might influence the alternate bearing in fruit trees.…”
Section: Introductionmentioning
confidence: 99%
“…Turkey is one of the most important fruit producers in the world and the country not only has great diversity in the number of fruits grown, but also an astonishing quantity of total produce, about 18 million tons. The fruits grown in Turkey mainly consist of pome fruits, stone fruits, berries and citrus (Acar et al, 2006;Ercisli et al, 2008;Serce et al, 2010;Guney 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have also applied PGRs externally to pistachios in order to prevent abscission, obtain regular yield, and increase flower bud formation (Acar et al, 2006;Lovatt et al, 2006;Askari et al, 2011;Oguz and Akkus, 2012;Padmalatha et al, 2017). However, some researchers did not report effective results (Ulger, 1997) due to insufficient data on the changes in PGRs and their relationship with alternate bearing in these species.…”
Section: Introductionmentioning
confidence: 99%
“…However, microscopic examinations performed by us had shown that the rupturing layer in pistachio flower buds began to form in the last week. Evidence in various fruit species has been shown that PGRs have significant effects during the growth and development periods that they particularly control abscission (Lavee, 1989;Aziz et al, 2001;Baktir et al, 2004;Cetinkaya, 2004;Acar et al, 2006;Gomez-Jimenez et al, 2010;Okay et al, 2011;Gundesli et al, 2019). However, the importance of PGRs and the regulation of metabolic transformations are still largely unknown in fruit trees showing alternate bearing.…”
Section: Discussionmentioning
confidence: 99%